Designing virtual environments for breath-awareness and eliciting positive affective states - Kitson, Alexandra; Prpa, Mirjana; Riecke, Bernhard E. (3rd Annual Innovations in Psychiatry and Behavioral Health: Virtual Reality and Behavior Change, 2017)
Breathing and affect are closely related: our breathing patterns can indicate our affective state, and changing breathing patterns can lead to a change in affect. A vast number of studies on mindfulness meditation and computer-supported mindfulness in virtual environments (VEs) have focused on using breath awareness as a feedback mechanism that the user can attend to for meditation, leading to overall decreased negative affect, e.g., stress, and increased well-being. However, the question remains: what exactly is the relationship between breath and audio/visual mappings in VEs, and those interaction paradigms, that contribute to eliciting positive affective states? We offer some design guidelines from having created two virtual experiences for breath-awareness and eliciting positive affective states.The first experience, [removedForReview], is an immersive soundscape that supports mindfulness-like awareness for novice meditators in a playful way by controlling sounds using their breath. The second, [removedForReview], is a VE that teaches novice meditators how to meditate by utilizing their breathing and EEG data through complementary visual and auditory feedback in order to reduce stress. While both of these VEs reduced participants’ stress levels, their interaction paradigms, mappings of breath to the elements in the environment, and overall user experiences are quite different. For that reason, we have compared the designs of our VEs and paired it with the feedback that we received from participants with the aim to understand the relationship between interaction paradigms and breath to audio/visual mappings, and elicitation of positive affective states.
Keywords: Riecke; Riecke_2017; affective-VR; alex-kitson; bernhard-riecke; mirjana-prpa; poster; posterWithoutPaper; pulse-breath-water; talkWithoutPaper